2022
DOI: 10.1038/s41558-021-01276-3
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced risk of concurrent regional droughts with increased ENSO variability and warming

Abstract: Spatially compound extremes pose substantial threats to globally interconnected socialeconomic systems. We use an Earth system model large ensemble to examine the future risk of compound droughts during the boreal summer over ten global regions with highly seasonal climate. Relative to the late-20 th century, the probability, mean extent and severity of compound droughts increase by ~60%, ~10% and ~20% respectively by the late-21 st century, with a disproportionate increase in risk across North America and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 74 publications
0
39
0
Order By: Relevance
“…Results indicated that ENSO patterns affected a similar area within most regions with enhanced magnitudes in all climate indicators, which inferred that the variability of ENSO interconnection remained largely static with warming [62,73]. Given the dominant role of multivariate ENSO events in determining drought events in a warmer climate, these findings emphasized the significance of the current ENSO-drought association and the related mechanisms [69,74,75]. For instance, the dynamic variabilities in SASM precipitation usually resulted in extreme wet and dry episodes, leading to flooding and drought events, respectively, with devastating socio-economic impacts [10].…”
Section: Scpdsi Possible Linkages With Different Climate Factors and ...mentioning
confidence: 81%
See 2 more Smart Citations
“…Results indicated that ENSO patterns affected a similar area within most regions with enhanced magnitudes in all climate indicators, which inferred that the variability of ENSO interconnection remained largely static with warming [62,73]. Given the dominant role of multivariate ENSO events in determining drought events in a warmer climate, these findings emphasized the significance of the current ENSO-drought association and the related mechanisms [69,74,75]. For instance, the dynamic variabilities in SASM precipitation usually resulted in extreme wet and dry episodes, leading to flooding and drought events, respectively, with devastating socio-economic impacts [10].…”
Section: Scpdsi Possible Linkages With Different Climate Factors and ...mentioning
confidence: 81%
“…For instance, the dynamic variabilities in SASM precipitation usually resulted in extreme wet and dry episodes, leading to flooding and drought events, respectively, with devastating socio-economic impacts [10]. The magnitude and onset timing of monsoon precipitation are uncertain, which often results in extreme events such as droughts and floods in SA regions [69,74]. Next, we studied changes in the effect of ENSO and IOD on the scPDSI variability in the study regions (see Figure 9a-c).…”
Section: Scpdsi Possible Linkages With Different Climate Factors and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…High temperature and drought are the main abiotic stressors affecting agricultural production in the context of global warming (Loka et al, 2020). By the middle and end of the 21st century, the temperature was predicted to rise by 2.8 ± 0.4°C and the probability of droughts during the boreal summer would increase by 40–60% (Brown & Caldeira, 2017; Singh et al, 2022). The combination of elevated temperatures and drought is expected to occur more frequently and sustain longer than in the past (Singh et al, 2022; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the compounding event (defined as spatially and temporally co‐occurring extremes) of Hurricane Ida occurring during the COVID‐19 pandemic resulted in excess mental health burden for the directly impacted population in the acute impact phase (i.e., 4 months post‐disaster) (Singh et al., 2022 ). We further this aim by also exploring the effects of mental health across multiple temporal periods (e.g., 4‐week, 3‐month, and 4‐month).…”
Section: Introductionmentioning
confidence: 99%